Dark pool trading with varying tick size, lot size and pricing rule : an experiment - Sharma, Uday (Nanyang Technological University, 2021)
Dark pools are decentralized trading venues where financial securities are traded without pre-trade transparency. Although initially used primarily by institutional investors, dark pools have been gaining popularity among retail traders. Using an experimental approach, we studied the performance of markets in the presence of dark pools when varying tick size, introducing institutional traders, and using alternate pricing mechanisms in the dark pool. We had eight separate experimental treatments. Data collected from sixteen sessions showed that widening the tick size decreases the price efficiency in the market, and this was largely contributed by the uninformed traders in the lit market. Further, we found that compared to retail traders, institutional traders prefer using dark pools and aggressive orders. This was because lot size restrictions reduced the bid-ask spread prevalent during transactions. Finally, we found that using an alternate pricing mechanism in the dark pool affects the market liquidity, but not the price efficiency.